Clinico-epidemiological study cf skin lyarts among patientsattending Tikrit teaching hospital - Najm, Khansaa; Hamed, Mazin; Abdul-Aziz, Ahmed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Back ground : Warts are benign epidermal neoplasms that are caused by human papilloma virus (HPVs). Warts are transmitted by touch; it may occur on adjacent toes ("kissing lesions"), or at sites of trauma at the hands, in periungual regions as a result of nail biting, and on plantar . surface. There are different clinical types as Common warts (Verruca vulgaris) begin as smooth, flesh-coloured papules and evolve into dome-shaped, gray-brown, hyperkeratotic growths with black dots on the surface ( thrombosed capillaries).The hands are the most commonly involved areas, but they may be found on any skin surface. Patients and methods: One hundred and twenty four (124) patients with warts were encountered in the outpatient clinic of dermatology at Tikrit Teaching Hospital from October 2008 to May 2009.Patients were examined by dermatologists and medical history was taken using special questionnaire. Results: from 124 patients , 68 (54.8%) were males. Preschool and primary school children were the most age group affected (41 %). Most frequent of wart cases were from urban (62%). The hands was the most frequent site in the body affected (24%). The most frequent wart type was a common wart (54.8%). Regarding the associated diseases atopic dermatitis was the most frequent (12%). Conclusion: The most frequent wart type was a common wart (54.8%)and The hands was the most frequent site in the body affected(24%).